The pragmatic function of illocutionary acts in children’s narrative: A study of The Tale of Peter Rabbit - Citra Ratu Angelia Mustika Sari; Eva Utami Durahman; Cecep Agus (Universitas Merdeka Malang, 2026)
This study examines the use of illocutionary acts in the children’s story The Tale of Peter Rabbit by Beatrix Potter, based on the classification proposed by John Searle. Speech acts are important in understanding how characters use language to achieve communicative purposes within a narrative. Therefore, this study aims to analyze how illocutionary acts are expressed through the characters’ dialogue and how they function pragmatically in the story. The study focuses on two main types of illocutionary acts, namely representatives and directives, as they frequently appear in the narrative. The data were taken from the text of The Tale of Peter Rabbit and analyzed by identifying relevant utterances, examining their linguistic forms, interpreting their contextual meanings, and explaining the speaker’s intentions. The findings show that representative and directive acts are used to convey information, give instructions, and express authority, especially through adult characters such as Mrs. Rabbit and Mr. McGregor. These illocutionary acts also produce perlocutionary effects, which are reflected in the characters’ responses and actions, contributing to plot development and moral lessons in the story. In conclusion, the use of speech acts in children’s narratives not only serves communicative functions but also plays an important role in conveying educational values beyond the surface meaning of the text.